Implementation and Application of Automata 18th International Conference, CIAA 2013, Halifax, NS, Canada, July 16-19, 2013. Proceedings - Konstantinidis, Stavros; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed papers of the 18th International Conference on Implementation and Application of Automata, CIAA 2013, held in Halifax, NS, Canada, in July 2013. The 25 revised full papers presented together with 3 invited papers and 7 short papers were carefully selected from 43 submissions. The papers cover various topics such as complexity of automata; compressed automata; counter automata; dictionary matching; edit distance; homing sequences; implementation; minimization of automata; model checking; parsing of regular expressions; partial word automata; picture languages; pushdown automata; queue automata; reachability analysis for software verification; restarting automata; transducers; tree automata; weighted automata; XML streams.
Complexity of automata -- Compressed automata -- Counter automata -- Dictionary matching -- Edit distance -- Homing sequences -- Implementation -- Minimization of automata -- Model checking -- Parsing of regular expressions -- Partial word automata -- Picture languages -- Pushdown automata -- Queue automata -- Reachability analysis for software verification -- Restarting automata -- Transducers -- Tree automata -- Weighted automata -- XML streams.
Keywords: Computer science; Data structures (Computer science).; Computer software; Information storage and retrieval systems; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Computational Biology/Bioinformatics.; Data Structures; Information Storage and Retrieval